2015
DOI: 10.1021/acs.inorgchem.5b00989
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Synthesis and Electronic Structure of a New Superconducting Strontium Germanide (SrGe3) Containing Ge2 Dumbbells

Abstract: We obtained a new strontium germanide (SrGe3) by high-pressure and high-temperature synthesis. It was prepared at 13 GPa and 1100 °C. The space group and cell constants are I4/mmm (No. 139), a = 7.7800(8) Å, c = 12.0561(13) Å, and V = 729.74(17) Å(3). SrGe3 crystallizes in the CaSi3 structure composed of Ge-Ge dumbbells and Sr(2+) ions. SrGe3 is a type II superconductor with a transition temperature of 6.0 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…The new samarium germanide is synthesized by highpressure high-temperature treatment of pre-reacted Sm 25.4 Ge 74.6 mixtures. The average chemical composition of the product as determined by energy dispersive X-ray spectroscopy amounts to Sm 25.5(5) Ge 74.5 (5) or SmGe 2.92 (8) .…”
Section: Composition and Propertiesmentioning
confidence: 99%
“…The new samarium germanide is synthesized by highpressure high-temperature treatment of pre-reacted Sm 25.4 Ge 74.6 mixtures. The average chemical composition of the product as determined by energy dispersive X-ray spectroscopy amounts to Sm 25.5(5) Ge 74.5 (5) or SmGe 2.92 (8) .…”
Section: Composition and Propertiesmentioning
confidence: 99%
“…Average interatomic distances d (Ge–Ge) versus the number of Ge–Ge contacts between 2.5 and 3 Å of selected alkaline-earth or rare-earth germanides. ,,, The values for the two-connected Ge atoms in the Ge1 chains as well as the average value for the five-connected framework atoms Ge2 and Ge3 fall into the typical ranges observed for similar structure motifs. ,,, , …”
Section: Resultsmentioning
confidence: 88%
“…The application of high-pressure methods to these binary systems led to the discovery of new structural patterns, especially for tetrel-rich compositions. These metastable high-pressure phases often exhibit multicenter interactions and combine covalent partial structures of the p-block element with metal-type electrical conductivity. In the series of rare-earth metals, lutetium, usually occurring as Lu 3+ in compounds, provides the absence of a magnetic momentum, setting the stage for the occurrence of superconductivity in these so-called covalent metals.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature and zero-field, the value for BaSi 3 amounts to ρ 300 K = 2906 μΩ cm with a residual resistance ratio (RRR) ρ 293 K / ρ 4 K = 1.5. In comparison to analogue high-pressure phases of germanium [12,13,19,27], the resistivity is high and shows only weak temperature dependence which is typical for polycrystalline silicides [60]. The changes of both resistivity and susceptibility below 6 K are attributed to traces of superconducting BaSi 2 [61].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic study of tetrel connectivities in polyanions revealed a variety of motifs with composition MT 3 ( M = Ca, Sr, Ba, Y, La, Ce, Eu, Gd, Tb, Ho, Er, Tm, Yb, Lu; T = Si, Ge) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. All of these exceed the scope of the 8- N rule and show interesting physical properties such as superconductivity.…”
Section: Introductionmentioning
confidence: 99%